PENERAPAN MODEL PEMBELAJARAN KOOPERATIF POE (PREDICT, OBSERVE, EXPLAIN) UNTUK MENINGKATKAN KETERAMPILAN PROSES PESERTA DIDIK DI MA AS-SALAM NAGA BERALIH KAMPAR - Nazmi Eliyarti; Muhammad Rahmad; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to determine the process skills students through the application of the POE model (Predict, Observe, Explain) on the material elasticity and Hooke's Law in class XI MIA MA As-Salam Naga Beralih Kampar. The research method used was Pre-Experimental design with the design of The One Shot Case Study. The subjects of the study were students of class XI MIA MA As-salam, totaling 36 students consisting of 19 female students and 17 male students. The data collection instrument used was a process skills test in the form of daily tests given to students after the learning process was carried out. Data were analyzed descriptively to provide a description of the participant's process skills expressed in terms of the percentage of descriptive statistics and the percentage of each indicator on the material elasticity and Hooke's Law. The results obtained from the percentage of descriptive statistics of students amounted to 76.22% and categorized high. Thus it can be concluded that the application of the POE model has a positive effect on the process skills of students in class XI MIA MA As-Salam Naga Beralih Kampar on the material elasticity and Hooke's Law.Key words : POE model, process skills students, elasticity and Hooke's Law.